2008
DOI: 10.1063/1.3046732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity of base fluid on thermal conductivity of nanofluids

Abstract: This study aims to investigate the effect of viscosity of the base fluid on the thermal conductivity of nanofluids in which Fe 3 O 4 nanoparticles are suspended in the base fluid composed of diesel oil and polydimethylsiloxane. Viscosity of the base fluid is varied by changing the volumetric fractions between both fluids. The measured thermal conductivity of nanofluids gradually approaches the value predicted by the Maxwell equation by increasing the viscosity. It demonstrates that the viscosity of nanofluids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…On the contrary,some studies suggested thatthe Brownian motion effect was important, such as Shukla et al [8].Sun et al [9,10] proposed that the micro convection effect due to the rotation of nanoparticles was the main reason for the effective thermal conductivity enhancement.Tsai et al [11] also reported that fora low viscous fluid, the Brownian motion of the nanoparticles was much active, which rendered the enhancement in thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary,some studies suggested thatthe Brownian motion effect was important, such as Shukla et al [8].Sun et al [9,10] proposed that the micro convection effect due to the rotation of nanoparticles was the main reason for the effective thermal conductivity enhancement.Tsai et al [11] also reported that fora low viscous fluid, the Brownian motion of the nanoparticles was much active, which rendered the enhancement in thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in temperature of the nanofluid was noted to have a weakening effect on the interparticle/intermolecule forces. It was reported that the slope of viscosity-temperature plot was pronounced in the range of [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] C, and the gradient was seen to increase with volume fractions. For high volume fractions, however, they could not provide a correlation that could simultaneously take into account temperature, particle concentration, and size effects on the relative viscosity.…”
Section: Effects Of Temperaturementioning
confidence: 99%
“…Tsai et al [33] studied the effects of viscosity of base fluids on thermal conductivity of nanofluids. The study was instrumental in understanding the interdependence of the thermal conductivity and viscosity.…”
Section: High Shearmentioning
confidence: 99%
“…Suspensions of the same Al 2 O 3 nanoparticles in water, ethylene glycol (EG), glycerol, and pump oil showed increase in relative thermal conductivity (k eff /k 0 ) with decrease in thermal conductivity of the base fluid [15,79,80]. On the other hand the alteration of the base fluid viscosity [81] (from 4.2 cP to 5500 cP, by mixing two fluids with approximately the same thermal conductivity) resulted in decrease in the thermal conductivity of the Fe 2 O 3 suspension as the viscosity of the base fluid increased. Comparative studies of 4 vol% SiC suspensions in water and 50/50 ethylene glycol/water mixture with controlled particle sizes, concentration, and pH showed that relative change in thermal conductivity due to the introduction of nanoparticles is ~5% higher in EG/H 2 O than in H 2 O at all other parameters being the same [68].…”
Section: B Base Fluidmentioning
confidence: 99%